The influence of polychronic time use on job satisfaction, work engagement, and turnover intention: a study of non-supervisory restaurant employees - Zhang, Wenhao (Kansas State University, 2015)
The present study examined polychronicity, an individual’s preference on engaging in multiple activities simultaneously as opposed to one at a time. In the restaurant setting, it is critical to understand whether a server prefers to engage in and switch among multiple tasks because it directly impacts the level of job satisfaction and work engagement the server experiences. The purpose of the study was to present a comprehensive view on relationships among time use preference, job satisfaction, work engagement, and turnover intention within a restaurant context. It was hypothesized that polychronicity positively predicted employee job satisfaction and work engagement and negatively predicted employee turnover intention. The sample of 251 respondents were full-time food and beverage servers working at full-service restaurants in the United States. A principle component factor analysis with varimax rotation was conducted to identify the factor structure of polychronicity, job satisfaction, work engagement, and turnover intention. Multiple regression analysis was utilized to empirically test the proposed hypotheses. The result of the analysis supported that polychronicity positively predicted job satisfaction and work engagement. In addition, both job satisfaction and work engagement negatively predicted turnover intention. However, the result did not support the hypothesized negative relationship between polychronicity and turnover intention. The findings of the study will assist restaurant managers in selecting candidates that best fit their organization. It will also assist employees in determining which career path best matches their personality traits. Managerial implications, limitations of this study, and direction for future study were discussed.
Keywords: Polychronicity; Job satisfaction; Work engagement; Turnover intention; Management (0454)